FoodSTART Africa – Eswatini. Harnessing the potential of nutritious sweetpotato to improve food and nutrition security - International Potato Center (International Potato Center, 2020)
The FoodSTART Africa project contributes to fighting malnutrition by promoting production and consumption of improved, nutritious sweetpotato varieties